1994
DOI: 10.1111/j.1467-8624.1994.tb00848.x
|View full text |Cite
|
Sign up to set email alerts
|

"Birds of a Feather...": Behavioral Concordances and Preferential Personal Attraction in Children

Abstract: The purpose of this study was to assess the extent to which preferential personal attraction was associated with behavioral similarity among newly acquainted children. Participants included 69 focal children, selected from a sample of 236 7-year-old children who met, for the first time, in same-sex quartets (n = 59) for a free-play session. Within each of these quartets, a "discriminating child" was identified; this child expressed a clear preference for one of his or her playmates over one other of her or his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0
4

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 20 publications
(14 reference statements)
7
41
0
4
Order By: Relevance
“…This study though, being cross sectional in design and not a probability sample, we can neither ascribe causation to any of the factors identified or confirm that the frequencies and proportions of the various attributes studied are representative of the general MSM population in Malawi. Furthermore, because of the snowballing nature of participant recruitment, it is likely that respondents recruited potential respondents who were similar to themselves or within their own sexual networks (Rubin et al, 1994). Study participants also self-reported in response to the questions asked.…”
Section: Discussionmentioning
confidence: 99%
“…This study though, being cross sectional in design and not a probability sample, we can neither ascribe causation to any of the factors identified or confirm that the frequencies and proportions of the various attributes studied are representative of the general MSM population in Malawi. Furthermore, because of the snowballing nature of participant recruitment, it is likely that respondents recruited potential respondents who were similar to themselves or within their own sexual networks (Rubin et al, 1994). Study participants also self-reported in response to the questions asked.…”
Section: Discussionmentioning
confidence: 99%
“…Anxious solitary children may have friends with similar behavioral tendencies. Indeed, evidence indicates that children tend to become friends with peers with whom they share behavioral characteristics (homophily) (Farver, 1996;Haselager, Hartup, van Lieshout, & Riksen-Walraven, 1998;Hogue & Steinberg, 1995;Rubin, Lynch, Coplan, Rose-Krasnor, & Booth, 1994). Although this effect has most often been demonstrated for conconcordance in aggressive behavior (Farver, 1996;Hanish, Martin, Fabes, Leonard, & Herzog, 2005), Rubin and colleagues have demonstrated that children develop preferences for interacting with playmates who resemble themselves with respect to rate of solitary behavior ; see also French, Jansen, Riansari, & Setiono, 2003;Haselager et al, 1998).…”
Section: Friends' Characteristicsmentioning
confidence: 99%
“…doi: 10.1016/j.jecp.2009.12.002 more opinions a child shares with another child, the more he or she will expect to like the other child. In addition, similarity in behavior has also been found to correlate with friendship during middle childhood (Haselager, Hartup, van Lieshout, & Riksen-Walraven, 1998) and even to predict attraction to peers in young school-age children (Rubin, Lynch, Coplan, Rose-Krasnor, & Booth, 1994). For example, 7-year-old children report more initial attraction to peers whose preferences (e.g., for activities or foods) are similar to their own (Reaves & Roberts, 1983).…”
Section: Introductionmentioning
confidence: 99%